A proteção dos direitos humanos do migrantes laborais em situação irregular no Brasil: análise do caso dos bolivianos explorados pela Zara - Lima, Georgia Marina Oliveira Ferreira de (2016)
Migration flows are a constant phenomenon in human history, which are enhanced by several factors, such as globalization and the complex cycle of economic and financial crisis. The Brazil, seen today on the world stage as an emerging country, has been increasingly sought by immigrants in search of better living conditions. These are attracted to positive expectations and sighted here employment opportunities, acceptance, tolerance and life changing. However, the expected is not always true because, despite being a signatory to the main international human rights treaties and advances in the treatment of this subject, there are still several flaws in the management of migrants in our country. There are still commonplace cases of a large number of Bolivians, especially those who are undocumented, working in conditions analogous to slavery and suffering various types of human rights violations. There is thus the interest in understanding the Brazilian position as to face these degrading situations. The hypothesis in this paper is that it takes place due to several factors, among which we highlight the absence of targeted public policies and the inconsistency between theory and practice. In this way, it will be investigated the reasons for the absence in Brazil of a current Migration Act and its opposite position to ratify the UN Convention on the Rights of Migrant Workers and Their Families Protection. It will also be checked so that institutions and civil society act to protect these labor migrants. Finally, this study aims to bring the limits, challenges and advances that Brazil has to build a satisfactory migration policy.